2021
DOI: 10.1007/s12035-021-02571-y
|View full text |Cite
|
Sign up to set email alerts
|

Ferrostatin-1 Alleviates White Matter Injury Via Decreasing Ferroptosis Following Spinal Cord Injury

Abstract: Spinal cord injury (SCI), a devastating neurological impairment, ubiquitously imposes a long-term psychological stress and high socioeconomic burden for the suffers and their family. To date, recent researchers have paid arousing attention to white matter injury and uncovering the underlying mechanism post-SCI. Ferroptosis, to our knowledge, has been revealed to be associated with diverse diseases including stroke, cancer, and kidney degeneration. However, its role in white matter damage after SCI remains uncl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 56 publications
8
46
0
Order By: Relevance
“…Ferroptosis has been previously reported a form of neuronal death in SCI. The pathogenesis of cell rupture, hemorrhaging, hemolysis, and supernumerary iron post SCI caused excess ROS accumulation, which results in ferroptosis occurrence ( Hu et al, 2021 ; Ge et al, 2022 ). Our results showed that ferroptosis-related protein GPX4, primarily expressed in neurons, significantly decreased while ACSL4 increased both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis has been previously reported a form of neuronal death in SCI. The pathogenesis of cell rupture, hemorrhaging, hemolysis, and supernumerary iron post SCI caused excess ROS accumulation, which results in ferroptosis occurrence ( Hu et al, 2021 ; Ge et al, 2022 ). Our results showed that ferroptosis-related protein GPX4, primarily expressed in neurons, significantly decreased while ACSL4 increased both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Given that, ferroptotic factors and ferroptosis-related signaling pathways have now been considered as potential diagnostic/prognostic biomarkers and therapeutic targets of NDDs. It is also worth-noting that ferroptosis has been reported to participate in neuroinflammation and neuronal death post-acute brain damage, which may play a role in the pathogenesis of NDDs as well ( Mao et al, 2020 ; Cao et al, 2021 ; Cui et al, 2021 ; Ge et al, 2022 ; Qu et al, 2022 ).…”
Section: Emerging Links Of Ferroptosis To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Oligodendrocytes are the main components of white matter formation and biological functions. In a recent study, it was found that in a rat model, ferrostatin-1 attenuated iron and ROS deposition in oligodendrocytes, inhibited their ferroptosis, attenuated white matter injury and promoted nerve conduction ( 121 ). In a similar study, it was revealed that in a model of RSL-3-induced ferroptosis in oligodendrocytes, liproxstatin-1 depressed mitochondrial membrane lipid peroxidation, restored GSH and GPX4 expression, thus showing stronger effect of blocking ferroptosis than DFO ( 122 ).…”
Section: Ferroptosis In Scimentioning
confidence: 99%